Pemberdayaan Masyarakat Dalam Pemanfaatan Aloe Vera dan Limbah Jelantah Untuk Meningkatkan Ekonomi Masyarakat di Desa Semolowaru Sukolilo Surabaya - Ratnawati, Susi; Rahmasari, Anggraeni; Radjak, Darwin Abd.; Purnama, Rangsang (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
Background, Training program on aloe vera drink manufacturing and utilization of jasmine oil for soap in Sukolilo District is an excellent initiative to empower the community, where it is expected to positively impact on economic empowerment in Sukolilopa diverse district through improvement of pempiteran. One of those commodities is in aloe vera and nettle oil. In creative hands aloe or aloe vera and safflower oil are conjured into fresh drinks and soaps of enormously enticing economic value. In fact, nowadays aloe vera drink has been able to penetrate the market all the way outside the island. Cultivation of aloe vera plant is becoming more and more common in society, making this a potential to be developed. Many people like aloe vera products this makes it a very suitable product to develop as well as be an alternative to increase the income of the people, especially the housewives to help reeconomize the family. Similarly, the utilization of lead waste into soap is an economic opportunity for the community. Methods : Training, practice as well as accompanying and monev in making aloe vera drink which has high economic value and can be sold in packaged form. And is a product that can be consumed daily with high nutritional value. Activity outcomes (1) Have skills in processing aloe vera drink as well as making soap from jasmine oil. (2). Produminman aloe vera varies flavors as well as attractive packaging, (3) Shariah-based enterprise management documents and affords venture development capital, (4) Publication in Journal of Devotion to society (5). Involve Students in MBKM as many as 2 students, equivalent to 3 Credits course Entrepreneurship Lectures